The impact of spatial resolution on area burned and fire occurrence projections in Portugal under climate change - Carvalho, Anabela (2010)
In this study, we investigated the impact of future climate change on fire activity in 12 districts across Portugal. Using historical relationships and the HIRHAM (High Resolution Hamburg Model) 12 and 25 km climate simulations, we assessed the fire weather and subsequent fire activity under a 2 x CO(2) scenario. We found that the fire activity prediction was not affected by the spatial resolution of the climate model used (12 vs. 25 km). Future area burned is predicted to increase 478% for Portugal as a whole, which equates to an increase from 1.4% to 7.8% of the available burnable area burning annually. Fire occurrence will also see a dramatic increase (279%) for all of Portugal. There is significant spatial variation within these results; the north and central districts of the country generally will see larger increases in fire activity.